Analysis of Homogeneity of Rainfall Data Between Stations in the Mapat River Catchment Area - Dani Helmi; Nurhayati Nurhayati; Danang Gunarto (Politeknik Negeri Lhokseumawe, 2025)
Abstract — Homogeneous rainfall data is essential in hydrological analysis because it affects the accuracy of calculations and modelling. Inhomogeneity can be caused by environmental changes, topographical differences, or recording errors; therefore, it is necessary to evaluate it before using the data in follow-up analysis. This study aims to test the homogeneity of rainfall data between stations in the Mapat River catchment area, Bengkayang Regency. The data used is the maximum daily rainfall for the period 1993–2022 from six stations: Dawar, Bengkayang, Sanggau Ledo, Karangan, Tebas, and Serukam. The data were directly tested for homogeneity using a two-sided t-test to compare the averages between station pairs at a significance level of 1%. The results of 15 combinations of station pairs showed that the total calculated t-value was smaller than the critical t (2.663), indicating that there was no significant difference in the average maximum daily rainfall between stations. The highest t-value was recorded in the Dawar–Bengkayang pair (2.19), which, although close to the critical limit, remained in the homogeneous category. These findings suggest that the variation in data is due to local climatic factors, rather than differences in instruments or recording methods. Complete homogeneity ensures the feasibility of data for a wide range of hydrological analyses, including river discharge modeling, flood analysis, and water resource management planning. The results of this study also demonstrate the consistency in the management of rain stations in the Bengkayang area over the past three decades.Keywords: rainfall data, homogeneity, double-sided t-test, Rainfall Catchment Area, Mapat River.